Effect of Social Media Language on Students’ Intention to Engage in Academic Use Behavior at Leading Universities in Nepal - Gunja Sah; Sajeeb Kumar Shrestha; Bhoj Raj Aryal (Language, Technology, and Social Media, 2025)
Social media plays a central role in students' daily academic activities across the globe. This study investigates how social media language influences students’ intention to engage in academic use behavior at leading universities in Nepal. Grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT), a structured questionnaire was distributed to 235 students from Tribhuvan University, Kathmandu University, Purbanchal University, and Pokhara University using stratified sampling. Structural Equation Modeling (SEM) was employed to analyze the data. Results reveal that performance expectancy significantly influences both behavioral intention and actual use behavior. Effort expectancy and social influence significantly affect use behavior but not behavioral intention, while facilitating conditions show no significant influence on either. Behavioral intention mediates the relationship between UTAUT constructs and use behavior. The findings highlight the importance of social media language in shaping students' academic engagement, offering practical insights for educators, policymakers, and platform developers to enhance social media’s educational utility.